Gamifying the Classroom: Enhancing Student Motivation and Engagement in Flipped Learning - Hadiprakoso , Raden Budiarto; Naufal, Farras Ahmad (Journal of Games, Game Art, and Gamification, 2025)
This study examines the impact of a multifaceted gamified application on first-year computer science students’ learning, motivation, and engagement in a flipped-learning environment covering data structures and algorithms. Thirty-one participants (17 M, 14 F; ages 18–20) completed a 10-item pre-test and Motivation & Engagement questionnaire, used our gamified app for three weeks, and then took a parallel post-test and the same questionnaire. Item analysis removed one invalid question and flagged another for poor discrimination, yielding a reliable post-test (Cronbach’s α = 0.89). Students’ correct answers rose from 17.0 (SD = 2.1) to 23.0 (SD = 1.8), a 35 % improvement confirmed by a paired t-test (t (30) = 15.27, p < 0.001, Cohen’s d = 2.76). Motivation scores increased from 73.4 (SD = 5.2) to 80.1 (SD = 4.8), and engagement from 75.2 (SD = 6.0) to 81.6 (SD = 5.5), both p < 0.001. A strong positive correlation (Spearman’s ρ = 0.65, p < 0.001) between the number of completed pre-class quizzes and post-test gains highlights the link between behavioral engagement and cognitive outcomes. These findings suggest that progress bars, leveling, challenges, leaderboards, and badges together satisfy students’ needs for competence, relatedness, and autonomy. Our results demonstrate that thoughtfully designed gamification can substantially enhance both affective and cognitive dimensions of flipped-learning in undergraduate STEM, offering practical guidelines for educators and paving the way for more rigorous, theory-driven implementations.